2+1 (2+2) Rempi-Tof Study of the Lowest Rydberg States (6s, 6s') of Methyl and Propyl Iodides. Issue 2 (1993) - Couris, S.; Agapaki, P.; Brint, Paul
Abstract : Resonance enhanced multiphoton ionisation (REMPI) combined with time of flight mass analysis under supersonic beam conditions has been used to investigate the nature of the UV absorption spectra broadening of the 6s Rydberg states in alkyl iodides. The increase of the size of the alkyl substituent was associated with this broadening although it was not known whether this was due to an increase in vibronic activity or to Rydberg state substituent interaction. The Jet cooled REMPI spectra of methyl and propyl iodide obtained have confirmed that the source of broadening of the 6s Rydberg states is solely due to vibronic activity of the alkyl group attached to the spectroscopic chromophore.